1966
DOI: 10.1037/h0020410
|View full text |Cite
|
Sign up to set email alerts
|

Research with the Wechsler Intelligence Scales for Adults.

Abstract: The past S years of research with the adult Wechsler scales is critically reviewed. Most investigators used the most recently developed scale, the Wechsler Adult Intelligence Scale. Topical coverage includes: comparative validity; short forms; special populations and applications; refinements and critiques; personality correlates; investigations of diagnostic value; special diagnostic groups; and scatter, patterns, and diagnosis. The 197 articles reviewed show that there is no diminution in the number of resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
19
0

Year Published

1968
1968
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(21 citation statements)
references
References 142 publications
2
19
0
Order By: Relevance
“…Because of this lateralized representation, the direction of the discrepancy may be useful for making diagnostic hypotheses about lesion loci. Guertin, Ladd, Frank, Rabin, and Hiester (1966) reviewed a number of studies suggesting that lower PIQ stores are indicative of righthemisphere pathology, whereas lower VIQ scores are indicative of damage to the left hemisphere, findings that are in agreement with the earlier reports of Reitan (1955) and of Klove and Reitan (1958). More recently, Uzzell, Zimmerman, Dolinskas, and Obrist (1979) reported differential effects on VIQ and PIQ scores corresponding to lateralization of intracranial hematoma or hemorragic contusion.…”
supporting
confidence: 76%
“…Because of this lateralized representation, the direction of the discrepancy may be useful for making diagnostic hypotheses about lesion loci. Guertin, Ladd, Frank, Rabin, and Hiester (1966) reviewed a number of studies suggesting that lower PIQ stores are indicative of righthemisphere pathology, whereas lower VIQ scores are indicative of damage to the left hemisphere, findings that are in agreement with the earlier reports of Reitan (1955) and of Klove and Reitan (1958). More recently, Uzzell, Zimmerman, Dolinskas, and Obrist (1979) reported differential effects on VIQ and PIQ scores corresponding to lateralization of intracranial hematoma or hemorragic contusion.…”
supporting
confidence: 76%
“…However, the significance of and even the generality of this finding have been subject to controversy (Fernald & Wisser, 1967;Guertin, Ladd, Frank, Rabin, & Hiester, 1966). While it seems that the Performance (P) > Verbal (V) sign should not be considered diagnostic of delinquency, it does represent one part of the cognitive or intellectual processes often associated with delinquency.…”
mentioning
confidence: 94%
“…After a review of the VIQ-PI& difference literature, Guertin, et al ( 3 ) concluded in essence that with the exception of possible use with brain-damaged clients, VIQ-PI& differences have minimal, if any, value in individual psychological assessment. Recently, Matarazzo (13) has offered a similar criticism of WAIS profile analysis, such as VIQ-PI& differences.…”
mentioning
confidence: 99%